HUBUNGAN GAYA HIDUP DENGAN HIPERTENSI PADA IBU HAMIL DI BLUD UPTD PUSKESMAS KONDA - IRDA, IRDAYANTI; asi, melania; Heyrani, Heyrani; Kartini, Kartini (Jurnal Stunting Pesisir dan Aplikasinya, 2025)
Introduction: Hypertension in pregnancy is one of the main causes of maternal and fetal morbidity and mortality, especially in developing countries. Hypertension in pregnancy is one of the obstetric complications that requires serious attention because it can have a negative impact on maternal and fetal health. The purpose of this study was to determine the relationship between lifestyle and hypertension in pregnant women at the BLUD UPTD Konda Health Center. Method: This type of quantitative observational study with a cross-sectional study design. The population was all pregnant women in the BLUD UPTD Konda Health Center working area, totaling 264 people. The sample consisted of 73 pregnant women. The instrument was a questionnaire. Data analysis used the chi-square test. Results: Of the 73 respondents, the most lifestyles were in the unhealthy category, as many as 42 people (57.5%), and the most hypertension was in the non-hypertensive category, as many as 37 people (50.7%). The results of data analysis obtained a value of X2 = 15.407 (greater than the value of X2 table = 3.841) and a p-value = 0.000 (? 0.05), so it can be concluded that there is a relationship between lifestyle and hypertension in pregnant women at BLUD UPTD Konda Health Center. Conclusion: There is a relationship between lifestyle and hypertension in pregnant women at BLUD UPTD Konda Health Center